2005
DOI: 10.1038/sj.mp.4001677
|View full text |Cite
|
Sign up to set email alerts
|

Association between 5-HTTLPR genotypes and persisting patterns of anxiety and alcohol use: results from a 10-year longitudinal study of adolescent mental health

Abstract: The serotonin transporter gene (5-HTT) encodes a transmembrane protein that plays an important role in regulating serotonergic neurotransmission and related aspects of mood and behaviour. The short allele of a 44 bp insertion/deletion polymorphism (S-allele) within the promoter region of the 5-HTT gene (5-HTTLPR) confers lower transcriptional activity relative to the long allele (L-allele) and may act to modify the risk of serotonin-mediated outcomes such as anxiety and substance use behaviours. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
52
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 47 publications
(56 reference statements)
12
52
0
Order By: Relevance
“…However, the current study found no significant relationships between 5-HTT genotype and age of onset of alcoholism, which is consistent with family-based studies reporting no differential association of the L or S allele with early onset of alcoholism in offspring (Samochowiec et al, 2006). Previous reports have suggested that the SS genotype is associated with increased anxiety and affective liability (Olsson et al, 2005) and may be associated with subtypes of alcoholism complicated by a comorbid psychiatric condition (Feinn et al, 2005). Though the current study included only patients without psychiatric comorbidity, we have reported, in another study of this population, that anxiety reduction is associated with a favorable treatment outcome (Sloan et al, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…However, the current study found no significant relationships between 5-HTT genotype and age of onset of alcoholism, which is consistent with family-based studies reporting no differential association of the L or S allele with early onset of alcoholism in offspring (Samochowiec et al, 2006). Previous reports have suggested that the SS genotype is associated with increased anxiety and affective liability (Olsson et al, 2005) and may be associated with subtypes of alcoholism complicated by a comorbid psychiatric condition (Feinn et al, 2005). Though the current study included only patients without psychiatric comorbidity, we have reported, in another study of this population, that anxiety reduction is associated with a favorable treatment outcome (Sloan et al, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…Ten studies estimating the associations of an interaction between the 5-HTTLPR genotype and an environmental factor with alcohol use and misuse were found, two that examined rhesus monkeys [28,30] and eight that examined humans [29,[31][32][33][34][35][36][37]. Descriptions of the studies are presented in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were longitudinal: one followed a sample from 15 to 22 years [31]; another followed a sample from 15.5 to 24 years [35]; and the final study followed participants from age 15 to 19 [33]. One study did not report the age of participants [32].…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations